Current evidence and applications of photodynamic therapy in dermatology - Wan MT; Lin JY (Dove Medical Press, 2014)
Marilyn T Wan,1 Jennifer Y Lin2 1Melanoma Program, Dana-Farber Cancer Institute, 2Department of Dermatology, Brigham and Women's Hospital, Harvard Medical School, Boston, MA, USA Abstract: In photodynamic therapy (PDT) a photosensitizer – a molecule that is activated by light – is administered and exposed to a light source. This leads both to destruction of cells targeted by the particular type of photosensitizer, and immunomodulation. Given the ease with which photosensitizers and light can be delivered to the skin, it should come as no surprise that PDT is an increasingly utilized therapeutic in dermatology. PDT is used commonly to treat precancerous cells, sun-damaged skin, and acne. It has reportedly also been used to treat other conditions including inflammatory disorders and cutaneous infections. This review discusses the principles behind how PDT is used in dermatology, as well as evidence for current applications of PDT. Keywords: photodynamic therapy, skin cancer, actinic keratosis, acne, aminolevulinic acid, methylaminolevulinate